HUBUNGAN KARAKTERISTIK DEWAN KOMISARIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPANRISK MANAGEMENT COMMITTEE(RMC) SECARA SUKARELA (Studi Empiris pada Perusahaan Non-Finansial di BEI Tahun 2009-2011) - Wiradharma, Ramanda Yura; Muid, Dul (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the effect of Board Commissioner characteristic and Firm characteristic to Risk management committee on non financial firms. Independent variabel used in this study is board experience, board size, leverage, firm size, and firm complexity. independency board commissioner, board size, management ownership, ownership concentration and leverage. This study also used firm size as control variables.Samples of this study were non financial firms listed on Indonesia Stock Exchange for the observation period of 2009 until 2011. Samples were collected by purposive sampling method and resulted 345 samples. This study used logistic regression for analyzing data.The result revealed that board size has positive and not significant to estabilishment of RMC and influential positive andsigniﬁcant to estabilishment of SRMC. Board experience has positive and not significant to estabilishment of RMC and influential positive andsigniﬁcant to estabilishment of SRMC. Leverage has negative and significant to estabilishment of RMC and influential negative andsigniﬁcant to estabilishment of SRMC. Firm Size has positive and not significant to estabilishment of RMC and influential positive andsigniﬁcant to estabilishment of SRMC. Firm Complexity has positive and not significant to estabilishment of RMC and influential negative and not signiﬁcant to estabilishment of SRMC.